Analysis of the Pemberdayaan Kesejahteraan Keluarga (PKK) Program as an Effort to Improve Family Well-Being in Rural Areas - Melani Nur Cahya (P3M STAI Kuningan, 2024)
Background: The Pemberdayaan Kesejahteraan Keluarga (PKK) program serves as a critical community-based empowerment mechanism in Indonesia, yet its implementation varies significantly across different local contexts. Understanding these contextual variations is essential for optimizing family-centered development strategies and strengthening local governance systems.Objective: This study aims to examine the implementation of the PKK program across three distinct local settings—Minahasa Regency (North Sulawesi), Serang City (Banten), and Cibinuang Village in Kuningan Regency (West Java)—to understand how PKK functions as a community-based empowerment initiative under diverse social and institutional conditions.Method: A qualitative descriptive approach with a case study design was employed. Data were collected through in-depth interviews, participatory observations, and document analysis across the three research sites.Findings and Implications: The study reveals that PKK program success is strongly determined by four key factors: local government support, cadre capacity, community participation levels, and structured data-driven planning mechanisms. Minahasa Regency demonstrates robust institutional support and well-structured program execution. Serang City shows promising organizational reform but encounters challenges in innovation capacity and equitable distribution of resources.Conclusion: PKK plays a strategic role in advancing inclusive, family-centered development in Indonesia. This study provides critical insights for strengthening local governance frameworks and enhancing social empowerment programs through context-sensitive approaches that address institutional capacity, participatory mechanisms, and collaborative governance structures.